Efforts to Increase Children's Motivation to Learn the Quran Through Audio-Visual Learning Media During the Covid-19 Pandemic - Alfipah, Mulan; Basri, Samsul (Jurnal Pengabdian Nusantara, 2024)
This article aims to provide motivation, especially for children in learning the Qur'an through audio-visuals, so that children remain enthusiastic about learning the Qur'an during the Covid-19 pandemic. During the Covid-19 pandemic, teaching and learning activities in face-to-face meetings are very limited, especially in learning the Qur'an, the lack of student understanding of the Qur'an is very influential. So, the activities of studying the Qur'an are not optimal and boring. In this study using a qualitative method, which has natural characteristics (natural setting) as a source of direct and descriptive data. Researchers in this case apply several techniques, namely Interview and Observation. The results showed that through audio-visual media in learning so that there was motivation given to children in understanding the learning of the Qur'an which was able to increase the enthusiasm of children in learning the Qur'an. With audio-visual media in learning is present as an answer that can increase effective learning motivation so that in the heart of every child always grows a love for the Qur'an.